2016
DOI: 10.1093/pubmed/fdw030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on multiple sclerosis: a meta-analysis

Abstract: Smoking habits are significantly associated with MS, although the association is not very strong. However, there is a dose-response relationship between the smoking habits and MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 50 publications
1
46
2
1
Order By: Relevance
“…We chose to include a number of sociodemographic and lifestyle variables likely to be associated with both neuroticism and suicide: unemployment, 28 , 32 , 37 , 41 community economic deprivation, 30 , 32 , 37 , 39 social support, 31 , 38 living with a spouse or partner, 32 , 35 , 42 living with a child, 32 , 35 , 42 cigarette smoking, 20 , 23 , 24 , 26 alcohol use, 19 , 22 , 25 and stressful life events in the past 2 years, including getting divorced, 32 , 33 , 35 the death of a spouse or partner 61 , 62 and financial difficulties. 30 , 32 , 37 , 63 Categorical covariates were coded such that the hypothesised risk or protective factor for suicide was coded as 1 (present) and 0 (absent).…”
Section: Methodsmentioning
confidence: 99%
“…We chose to include a number of sociodemographic and lifestyle variables likely to be associated with both neuroticism and suicide: unemployment, 28 , 32 , 37 , 41 community economic deprivation, 30 , 32 , 37 , 39 social support, 31 , 38 living with a spouse or partner, 32 , 35 , 42 living with a child, 32 , 35 , 42 cigarette smoking, 20 , 23 , 24 , 26 alcohol use, 19 , 22 , 25 and stressful life events in the past 2 years, including getting divorced, 32 , 33 , 35 the death of a spouse or partner 61 , 62 and financial difficulties. 30 , 32 , 37 , 63 Categorical covariates were coded such that the hypothesised risk or protective factor for suicide was coded as 1 (present) and 0 (absent).…”
Section: Methodsmentioning
confidence: 99%
“…Cigarette smoking is a well‐established risk factor for MS onset, with a clear dose–response relationship . Age at starting smoking does not seem to affect MS risk .…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…66 Another recent study provided information regarding the effects of different smoking habits on MS risk, indicating a dose-response relationship between these two variables. 67 It was deduced by one study that the increased MS risk associated with smoking remains up to 5 years after cessation of smoking. 68 The effect of maternal smoking on MS risk is not clarified yet, but one case control study showed a higher risk, 69 and a second showed no association.…”
Section: Environmental Factorsmentioning
confidence: 99%